Design of Compact Open-Ended Wrench-Shaped Patch Antenna for 5G Sub-6 GHz Band Applications - Hassan, Mahadi; Islam, Abu Zafor Muhammad Touhidul (Journal of Electronics and Electrical Engineering, 2025)
The 5G network requires higher frequency bands as the Sub-6 GHz to handle vast amounts of data and to provide larger bandwidth. This study proposes a novel open-ended wrench-shaped patch antenna with small dimensions of 24 × 32 × 1.6 mm3 to achieve wideband operation in the Sub-6 GHz range. The antenna is etched onto an FR-4 substrate and has dimensions of 1.6 mm in height, a loss tangent of 0.025, and a relative permittivity of 4.3. The intended antenna is excited by a 50 Ω microstrip line, and the simulation is performed using CST software. The impedance matching and antenna bandwidth are improved by introducing a slotted patch plane with a defective ground structure. With two resonance frequencies of 3 GHz and 4.55 GHz, the suggested antenna has a gain of 1.91 dB to 2.90 dB, a directivity of 2.62 dB to 4.13 dB, a return loss of −58.5 dB and −28.4 dB, and a VSWR of 1.002 and 1.08. The wrench’s open-ended design provides a broad 3.2 GHz impedance bandwidth and a maximum radiation efficiency of 85.7% in the frequency range of 2.6 to 5.8 GHz, encompassing multiple crucial bands utilized for various applications, including 5G. The design offers significant size reduction while maintaining excellent performance characteristics suitable for 5G wireless devices operating frequency of Sub-6 GHz. The suggested antenna has been built as an experimental prototype, and the results of the measurement and modeling of the return loss parameter coincide quite well.